The Impact Of Changes In Legal Acts On Electronic Certificates - Nugroho, Abraham Odilo; Rahayu, Etty Tri; Saraswati, Harsinta; Rukmana, Siti (PALAR (Pakuan Law review), 2025)
ABSTRACTThis article aims to analyze the impact of changes in legal acts on electronic certificates in people's lives as a form of dissemination of information to the public in connection with changes in provisions regarding electronic certificates regulated in the Regulation of the Minister of State for Agrarian Affairs / Head of the National Land Agency Number 3 of 2023 concerning the Issuance of Electronic Documents in Land Registration Activities which has been in effect since July 2024. The main problem in this article is how the legal impact of changing electronic certificates from analog certificates to electronic certificates. The method of analyzing the article with normative legal research is explanatory in nature using primary and secondary legal materials, and the form of research used is prescriptive. The results of the study concluded that the impact of changes in legal acts on electronic certificates has positive and negative impacts in society. So that the suggestions given in this article are expected to help and educate the public who need education regarding the legal impact of changes in electronic certificates in Indonesia.  Keywords: Certificate, Electronic Certificate, National Land Agency.